An environmental scan of residential treatment service provision in Ontario - Farihah Ali; Justine Law; Cayley Russell; Nikki Bozinoff; Brian Rush (BMC, 2023)
Abstract Background Ontario has one of the highest rates of substance-related harms in Canada. Residential treatment programs in the province provide a variety of in-house treatment services to support the needs of individuals with substance use disorders (SUD). However, these programs are not standardized, often varying in the type, quality, and availability of services offered, including evidence-based interventions such as Opioid Agonist Treatment (OAT). Local treatment systems are also rather fragmented and complex to navigate, creating barriers for potential services users to identify and make informed choices on available treatment options. Methods Between May to August 2023, we conducted an environmental scan to capture available information on all publicly-funded residential treatment programs in Ontario using the ConnexOntario service portal, a government-funded, health services information platform. Data were captured on organization name, geographical location, program description, program type (residential addictions treatment or supportive recovery programs), eligibility criteria, target population, the program's OAT policies, number of available beds, minimum and maximum length of stay, projected wait times, funding source, and associated fees for program admission. Data were extracted and organized by geographic region, and findings were presented descriptively. Results A total of 102 residential addiction treatment programs and 36 residential supportive recovery programs in Ontario were identified. The scan noted substantial regional variations in program availability and wait times, along with a lack of programs tailored to unique populations such as women, youth, and Indigenous peoples. There is also a paucity of publicly-available information on program offerings, including detailed specifics on OAT policies within residential treatment programs that are crucial to ensuring that the services being offered are safe and grounded in evidence-based practice. Conclusions Findings from the scan highlight notable gaps in program types, offerings, and availability among residential treatment programs in the province, including a lack of standardization on OAT policies across programs. Efforts should be made to ensure access to treatment-specific program information relevant to potential service users and to enhance coordinated access to residential treatment services in the province.